Reconsidering Racial and Ethnic Discrimination in Indonesia’s Criminal Law Reform from an Islamic Human Rights Perspective - Marfu’ah Latifatuzzahro; Eva Mir’atun Niswah (CV. Dyoqu Publishing and Management, 2025)
Abstrak Background: Indonesia’s 2023 Criminal Code introduces explicit criminal provisions on racial and ethnic discrimination in a diverse society where identity based conflict has not disappeared. The reform, however, still invites debate on whether it offers real safeguards for victims or mainly reinforces equality in formal terms. Aims: This article revisits the construction and punishment of racial and ethnic discrimination in KUHP 2023, focusing on Articles 244 and 245, and tests their normative coherence against Islamic human rights principles. Methods: Using normative doctrinal analysis and a statute approach, the study examines KUHP 2023 in relation to the previous KUHP framework and Law No. 40 of 2008 on the Elimination of Racial and Ethnic Discrimination. The discussion draws on scholarly literature and evaluates definitions, scope, and sanction design through Islamic principles of human dignity, equality, justice, freedom, peace, and social security. Result: KUHP 2023 strengthens recognition of discriminatory conduct and treats discriminatory motives as relevant to sentencing, including through aggravation where serious offences are involved. At the same time, the offence design remains comparatively narrow and the penalty scale may be insufficient to deter conduct that produces broader social harm. From an Islamic human rights perspective, the provisions reflect dignity and equality, yet they require a clearer orientation toward victim protection and substantive justice. Conclusion: The reform is an important advance, but further doctrinal refinement is needed so anti discrimination rules operate as effective protections consistent with Islamic human rights values, not merely as symbolic prohibitions.